Differences Between Women and Men in Phase I Cardiac Rehabilitation After Acute Myocardial Infarction: A Nationwide Population-Based Analysis. Issue 3 (January 2016) - Lin, Wen-Chih; Ho, Chung-Han; Tung, Li-Chen; Ho, Chi-Che; Chou, Willy; Wang, Chun-Hou
Abstract : Abstract: Although numerous studies have investigated gender-related differences in patients who have had an acute myocardial infarction (AMI), few studies have examined the gender-related differences among inpatients receiving Phase I inpatient cardiac rehabilitation following AMI. Using data from the Taiwan National Health Insurance Research Database, this study analyzed 6713 adult patients who received inpatient cardiac rehabilitation following AMI between 2002 and 2011. The differences in comorbidity, medical service use, and prognosis between the male and female patients were analyzed to determine whether the comorbidities affecting their prognoses differed. Female patients accounted for 23.18% of the sample, had a higher average age, and exhibited severe comorbidities; furthermore, they had significantly more days of hospitalization and days in an intensive care unit than did male patients. The gender-related differences in hospital mortality rate and 30-day mortality rate were nonsignificant, but female patients exhibited a significantly higher 1-year mortality rate. Moreover, the risk for 1-year mortality was higher among female patients with moderate or severe renal disease (odds ratio: 1.94, 95% confidence interval: 1.29–2.92) than among their male counterparts. However, the 1-year mortality rate for the female patients did not increase after all risk factors were adjusted. Gender-related differences in age, comorbidity, and prognosis were confirmed in AMI patients receiving Phase I inpatient cardiac rehabilitation. In addition, gender-related differences were observed in the comorbidity risk factors affecting prognosis. However, being female did not affect the prognosis.